Barriers and facilitators to asthma self‐management in adolescents: A systematic review of qualitative and quantitative studies. Issue 4 (7th October 2016) - Holley, Simone; Morris, Ruth; Knibb, Rebecca; Latter, Sue; Liossi, Christina; Mitchell, Frances; Roberts, Graham
Summary: Background: Many adolescents have poor asthma control and impaired quality of life despite the availability of modern pharmacotherapy. Research suggests that poor adherence to treatment and limited engagement in self‐management could be contributing factors. Objective: To conduct a systematic review of the barriers and facilitators to self‐management of asthma reported by adolescents using a narrative synthesis approach to integrate the findings. Design: MEDLINE, EMBASE, CINAHL, and PsycINFO were searched for all types of study design. Full papers were retrieved for study abstracts that included data from participants aged 12–18 years referring to barriers or facilitators of asthma self‐management behaviors. Results: Sixteen studies (5 quantitative and 11 qualitative) underwent data extraction, quality appraisal, and thematic analysis. Six key themes were generated that encompassed barriers and/or facilitators to self‐management of asthma in adolescents: Knowledge, Lifestyle, Beliefs and Attitudes, Relationships, Intrapersonal Characteristics, and Communication . Conclusions: There is a pressing need to prepare adolescents for self‐management, using age‐appropriate strategies that draw on the evidence we have synthesized. Current clinical practice should focus on ensuring adolescents have the correct knowledge, beliefs, and positive attitude to self‐manage their illness. This needs to be delivered in a supportive environment that facilitates two‐way communication, fosters adolescents' self‐efficacy to manage their disease, and considers the wider social influences that impinge on self‐management. Pediatr Pulmonol. 2017;52:430–442. © 2016 Wiley Periodicals, Inc.